Embryo development alteration in rats treated with lapachol - Juliana Maganha; Evelise de Souza Rocha; Marcos Antônio Fernandes Brandão; Vera Maria Peters; Martha de Oliveira Guerra (Brazilian Archives of Biology and Technology, 2006)
Lapachol, a naphthoquinone extracted from plants of the genus Tabebuia (family Bignoneaceae), showed multiple therapeutic activities. Pregnant Wistar rats were treated with Lapachol from the 1st to the 4th (pre-implantation period) and from 5th to 7th (implantation period) post insemination day (PID). Mothers were sacrificed on the 5th or on the15th PID. Number of corpora lutea, preimplantation embryo, blastocysts, live and dead fetuses and resorptions were counted. There were no signs of maternal toxicity. The number and the morphology of embryos, during oviduct development (pre-implantation period), did not seem to be affected by this drug, but during the implantation period, lapachol was toxic causing the death of embryos and intrauterine growth retardation. O Lapachol é uma naftoquinona, extraída de plantas do gênero Tabebuia (família Bignoneaceae), que apresenta múltiplas atividades terapêuticas. Estudos prévios sobre o efeito do lapachol no início do desenvolvimento embrionário de ratas são controversos. No presente trabalho ratas Wistar prenhes foram tratadas com lapachol do 1º ao 4º dias pós-inseminação (período de pré-implantação) e do 5º ao 7º dias (período de implantação do blastocisto). As mães foram sacrificadas no 5º o e no 15º dia pós-inseminação. Contaram-se corpos lúteos, embriões em fase de pré-implantação, blastocistos, fetos vivos e mortos e reabsorções.Fetos e placentas foram pesados. Não ocorreram indícios de toxicidade materna.O número e a morfologia dos embriões durante o desenvolvimento tubário não foi afetado pela droga, mas durante o período de implantação o lapachol foi tóxico, causando morte de embriões e retardo de crescimento intra-uterino.